SOMATIC VOCABULARY AS A REPRESENTATION OF THE LINGUISTIC WORLDVIEW: ASSOCIATIVE AND PHRASEOLOGICAL ASPECTS - Baktybek kyzy A. (Vestnik Issyk-Kulʹskogo universiteta)
The article deals with the problem of the origin of somatic phraseological units, as well as the syntactic organization of phraseological units with a somatic component in the Russian languages. Somatism in the Russian languages have great potential for the formation of phraseological units characterized by stability, high frequency of use. The conducted contrastive analysis indicates a significant similarity of the structural organization of the studied units in the Russian languages. Somatic vocabulary is one of the key elements shaping the linguistic worldview, as the human body serves as the most understandable and accessible object for observing and comprehending the surrounding reality. Words denoting body parts are widely used not only in their literal sense but also figuratively, forming a variety of idioms and set expressions that reflect cultural, religious, and philosophical aspects of human experience. The purpose of this article is to examine the associative and idiomatic aspects of somatic vocabulary and its role in representing the linguistic worldview. The author analyzes metaphorical idiomatic expressions in Russian, examining their structural and semantic features. Special attention is given to the cultural and linguistic specificity of idioms, emphasizing the influence of natural, every day, and religious conditions on the formation of idiomatic imagery. Idioms are viewed as reflections of the spiritual values of the people embedded in language, and their analysis provides a deeper understanding of the thinking, traditions, and culture of the Russian people through the prism of historical epochs.